Nano-phase separation sintering in nanostructure-stable vs. bulk-stable alloys - Park, Mansoo; Chookajorn, Tongjai; Schuh, Christopher A. (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
Accelerated sintering through nanoscale-phase separation is explored in the Cr-Ni binary system. When the processing requirements of both supersaturation and nanocrystallinity are met in the initial powders, Cr-Ni alloys show an onset of sintering at a low temperature and a rapid rate of densification. Independent characterization techniques, namely x-ray diffraction, thermomechanical analysis, and electron microscopy, confirm that Ni-rich phases develop upon sintering in a way that enhances consolidation. However, this system is shown to be unique in that the Ni addition facilitates rapid nano-phase separation sintering but does not promote stability of a nanoscale grain structure; the nanostructure is a transient feature of the system and the fully consolidated material is microcrystalline with a phase-separated structure. A thermodynamic stability analysis explains this structural evolution, and clarifies the roles of alloying elements that stabilize nanostructure and those that accelerate sintering in nanostructured systems. This work may broaden the applicability of nano-phase separation sintering and inform alloy design based on sinterability. (C) 2017 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: NICKEL-DOPED TUNGSTEN; NANOCRYSTALLINE ALLOYS; LIQUID-PHASE; MECHANICAL-PROPERTIES; GRAIN-GROWTH; SOLID-SOLUTION; BETA-BRASS; W SYSTEM; CR-NI; DENSIFICATION